Somos todos empregados de uma prisão sem grades: efeitos do trabalho na saúde dos empregados de uma instituição de pesquisa - Duarte, Renata Nogueira Machado (2019)
This study aimed to study the relationship between work and psychological suffering in the health of employees of a research organization, justifying the need to identify possible psychic aspects that workers mobilize in the face of the constraints and adversities that the work organization and can lead to illness and suffering. This research was a descriptive and exploratory case study, developed in the light of Work Psychodynamics, with a group of 10 (ten) workers. This group was chosen considering that, according to records of the Organization's Occupational Health Medical Control Program, they presented some type of psychological distress (anxiety, insomnia, depression, significant level of stress, among others) that affect them in terms of quality of life . For this, individual interviews were conducted with each of the identified employees. The interviews were recorded, transcribed and categorized into sense nuclei. The interviewees brought to the surface aspects of the organization of work that they perceive as being sick (unfairness of procedures, lack of speaking space, absence of a collective of workers, among others). Such situations brought to the interviewees a psychological suffering and, often, psychological damages of difficult control. As a result, it was possible to analyze the organization of work as a whole, the defensive and mobilization strategies, and the characterization of illness from the feelings and experiences of suffering manifested. The relevance of this work is contained in the importance of identifying possible causes and problems arising from the labor context, strengthening the framework of this knowledge in order to delineate preventive and corrective actions that benefit organization and employees, as well as contribute to the development of new studies on the theme.